Will the God Win?: The Case of the Buddhist Mummy. Issue 2 (23rd June 2017) - Liu, Zuozhen
Abstract: This article concerns the case of a stolen 1, 000-year-old Buddhist mummy, known as the statue of Zhanggong-zushi, which caught the attention of the international community. The statue of Zhanggong-zushi is the embodiment of God in the eyes of the locals, and the treatment of human remains is controversial and sensitive. This case opens a discussion as to how Western courts should consider religious interests in the disputes of stolen cultural property. It is very important for the art world to understand how locals feel about the loss of their culture or religion.